Seasonal Changes in the Vertical Structure of Ozone in the Martian Lower Atmosphere and Its Relationship to Water Vapor. Issue 10 (24th October 2022) - Olsen, K. S.; Fedorova, A. A.; Trokhimovskiy, A.; Montmessin, F.; Lefèvre, F.; Korablev, O.; Baggio, L.; Forget, F.; Millour, E.; Bierjon, A.; Alday, J.; Wilson, C. F.; et al.
Abstract: The mid‐infrared channel of the Atmospheric Chemistry Suite (ACS MIR) onboard the ExoMars Trace Gas Orbiter is capable of observing the infrared absorption of ozone (O3 ) in the atmosphere of Mars. During solar occulations, the 003←000 band (3, 000‐3, 060 cm −1 ) is observed with spectral sampling of ∼0.045 cm −1 . Around the equinoxes in both hemispheres and over the southern winters, we regularly observe around 200–500 ppbv of O3 below 30 km. The warm southern summers, near perihelion, produce enough atmospheric moisture that O3 is not detectable at all, and observations are rare even at high northern latitudes. During the northern summers, water vapor is restricted to below 10 km, and an O3 layer (100–300 ppbv) is visible between 20 and 30 km. At this same time, the aphelion cloud belt forms, condensing water vapor and allowing O3 to build up between 30 and 40 km. A comparison to vertical profiles of water vapor and temperature in each season reveals that water vapor abundance is controlled by atmospheric temperature, and H2 O and O3 are anti‐correlated as expected. When the atmosphere cools, over time or over altitude, water vapor condenses (observed as a reduction in its mixing ratio) and the production of odd hydrogen species is reduced, which allows O3 to build up. Conversely, warmer temperatures lead to water vapor enhancements and ozone loss. The LMD Mars Global Climate Model is able to reproduce vertical structure and seasonal changes of temperature, H2 O, and O3 that we observe. However, the observed O3 abundance is larger by factors between 2 and 6, indicating important differences in the rate of odd‐hydrogen photochemistry. Plain Language Summary: Ozone on Mars is part of the so‐called odd‐oxygen family of reactive, oxidizing gases. It is part of many chemical cycles that help convert one type of gas into another, facilitating the transfer of carbon or hydrogen. Odd‐oxygen is crucial to linking the cycles of water vapor and carbon dioxide, or the destruction of trace gases, such as methane. With the Atmospheric Chemistry Suite onboard the ExoMars Trace Gas Orbiter, we are able to study the vertical structure of ozone in the Martian atmosphere and make direct comparisons between it and water vapor and temperature. We have observed ozone abundances several times larger than predicted, suggesting that the oxidizing power of the Martian atmosphere is stronger or faster than expected. We have also observed and measured the relationship between these products: temperature controls the abundance of water vapor, and when the atmosphere cools and water condenses, ozone is able to build up. It is the by‐products of when water vapor breaks down in sunlight that remove odd‐oxygen from the atmosphere. Key Points: Observations of the vertical distribution of ozone on Mars over 3 years Direct comparison of water vapor, ozone, and temperature, revealing trends and correlations Ozone is observed in higher abundances than photochemical models predict